Modelos Estratégicos en marketing y emprendimiento para la economía naranja : un enfoque a casos colombianos. - Cantillo Guerrero, Ernesto (Corporación Universitaria Americana, 2023)
Modern organizations need to respond and adapt to the changing conditions of the context if they want to remain in the market. Among the tools to achieve this, marketing is the foundation to achieve the positioning of a business, a fact that is sometimes underestimated, especially in the world of new business ventures, because they have few resources and want to market directly without any effort. This motivated to write this book called "Strategic Models in Marketing and Entrepreneurship for the Orange Economy: an approach to Colombian cases", as a product of research in the field, where studies are made to identify the potential of the tools available to those in charge of the companies.